Bacterial infections, immune overload, and MMR vaccine. Issue 3 (1st March 2003) - Miller, E; Andrews, N; Waight, P; Taylor, B
Abstract : Combined measles, mumps, and rubella (MMR) vaccine did not increase the risk of hospitalisation with invasive bacterial infection in the three months after vaccination; rather there was a protective effect. These results provide no support for the concept of "immunological overload" induced by multiple antigen vaccinations, nor calls for single antigen vaccines.